En torno a la composición de tres cuentos fantásticos de José María Merino - Alvarez, Roxana Guadalupe Herrera [UNESP] (My University, 2014)
In this article, we undertake the reading of three fantasy short stories of the Spanish writer José María Merino by means of the theoretical propositions of Michel Lord and Juan Herrero Cecilia. These propositions attempt to elucidate the composition of the fantasy narrative delimiting a set of phases. This model applied to fantasy narrative arises from the perspective of Jean-Michel Adam on the composition of narrative texts in general.

En este artículo1 llevamos a cabo la lectura de tres cuentos fantásticos del escritor español José María Merino por medio de las propuestas teóricas de Michel Lord y Juan Herrero Cecilia. Esas propuestas intentan elucidar la composición del relato fantástico delimitando un conjunto de fases. Ese modelo aplicado al relato fantástico procede de la perspectiva de Jean-Michel Adam sobre la composición
Keywords: Fantasy Literature; José María Merino; Short story; Spanish Literature